Kjøpesentervakthold: Privatisering av kontroll? - Snertingdal, Mette Irmgard (Nordisk Tidsskrift for Kriminalvidenskab, 2002)
This article examines the extent to which private security has taken over police work. Shopping centers provide a particularly useful setting for the discussion of privatisation of control. This is because the division of labour between police and private guards in shopping centers has become increasingly unclear. Privatisation is generally understood as a shift in the responsibility for producing goods and services from the public sector to the private sector. My argument is that a special concept of privatisation, "offer privatisation ", is fruitful for analysing private security in shopping centers "Offer privatisation” refers to a situation in which the public sector fails to meet the demands of the people, and private actors offer to meet those demands. When private security in shopping centers is understood in light of the concept of "offer privatisation ", it raises the question of to what consequences this may lead. I explore two such consequences: Social discrimination and new social needs brought into focus. At the end of the article I discuss the authorities’ ’answer to the shop owners’ demand for control: Increasing the punishment for shoplifting. On the one hand, this proposal can be understood as an increase in legal protection for property rights. On the other hand, it is unclear whether the police or the private guards have been given the responsibility for its implementation. This lack of clarity is at least partially attributable to the failure of politicians to specify the border between public and private responsibility for control.